2011
DOI: 10.1039/c0cp01929a
|View full text |Cite
|
Sign up to set email alerts
|

High-resolution solid-state13C μMAS NMR with long coherence life times

Abstract: Longer coherence life times (i.e. smaller homogeneous linewidths) can be achieved for carbon resonances which are strongly coupled to protons with high rf field heteronuclear decoupling in micro magic angle spinning NMR. Better proton decoupling enhances the sensitivity and resolution of two-dimensional through-bond correlation experiments for mass-limited samples with uniform carbon labeling.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
20
1

Year Published

2012
2012
2018
2018

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(22 citation statements)
references
References 15 publications
1
20
1
Order By: Relevance
“…An interesting side note is that the measured R 1ρ of 0.18 s -1 for CH 2 in glycine should correspond to R 2 ' (minus the exchange contribution) under perfect heteronuclear decoupling conditions. Currently the smallest reported R 2 ' for CH 2 in glycine measured using 400 kHz SPINAL decoupling is ~4 s -1 , 23 which is still >20 times larger than the R 1ρ measured in this study. This result suggests that, even though it may be difficult to achieve, there is still plenty of room for improvement in heteronuclear decoupling methodology before the relaxation limit for coherence lifetimes is reached.…”
Section: Resultscontrasting
confidence: 70%
“…An interesting side note is that the measured R 1ρ of 0.18 s -1 for CH 2 in glycine should correspond to R 2 ' (minus the exchange contribution) under perfect heteronuclear decoupling conditions. Currently the smallest reported R 2 ' for CH 2 in glycine measured using 400 kHz SPINAL decoupling is ~4 s -1 , 23 which is still >20 times larger than the R 1ρ measured in this study. This result suggests that, even though it may be difficult to achieve, there is still plenty of room for improvement in heteronuclear decoupling methodology before the relaxation limit for coherence lifetimes is reached.…”
Section: Resultscontrasting
confidence: 70%
“…5 It has also been demonstrated that solid-state NMR experiments on single crystals can also reduce ABMS broadening. 10,11 Hexamethylbenzene (HMB) is the prototypical sample displaying ABMS broadening; both the methyl and aromatic carbon 13 C peaks have a FWHM greater than 1 ppm, and the FWHM of the peaks (in ppm) is independent of the applied field (vide infra). 5,6,12 Substantial ABMS broadening has also been clearly observed in the 13 C solid-state NMR spectra of porphyrins, 10 glycine, 11 metal-organic frameworks (MOF), 13 APIs with aromatic groups such as ibuprofen 7 and piroxicam HCl, 14 the 19 F solid-state NMR spectrum of octafluoronapthalene 8 and in the high resolution 1 H solid-state NMR spectra of organic materials obtained with combined rotation and multiple pulse spectroscopy (CRAMPS) 15 or ultrafast MAS (ν r > 100 kHz).…”
Section: Introductionmentioning
confidence: 99%
“…Obtaining high-resolution solid-state NMR spectra relies on many facts in addition to the decoupling sequence, including local order in the sample (as explored through production of nano-or microcrystals and highly order fibers [21][22][23][24] ), nuclear spin relaxation properties, 25 and multiple-spin effects. 26 While the former is an intrinsic property of the sample that only can be altered through sample preparation, the two latter may be influenced through the use of fast sample spinning serving to reduce, e.g., 1 H-1 H interactions.…”
Section: Introductionmentioning
confidence: 99%